A Survey on Stock market price prediction using data mining techniques - Purey, Prateek; Patidar, Anil (International Journal of Computer Sciences and Engineering, 2025)
data mining techniques are used in a number of applications such as classification, prediction and others. In this presented work the data mining techniques are investigated for implementing in prediction applications. Therefore this paper provides the study about the stock market price prediction techniques and the recently made contributions in domain of prediction using data mining techniques. The data mining techniques are having the ability to evaluate the historical stock market price trends and can approximate the upcoming market prices. In addition of that a model using available techniques is also presented work